2018
DOI: 10.1111/dmcn.14084
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure and neurological and behavioural functioning in infants born preterm

Abstract: AIM To examine: (1) relationships between brain structure, and concurrently assessed neurological and behavioural functioning, in infants born preterm at term-equivalent age (TEA; approximately 38-44wks); and (2) whether brain structure-function relationships differ between infants born very (24-29wks) and moderate-late (32-36wks) preterm.METHOD A total of 257 infants (91 very preterm, 166 moderate-late preterm; 120 males, 137 females) had structural magnetic resonance imaging (MRI) and neurological and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…These 11 studies included DTI data from 554 very preterm, 575 moderate-late preterm, and 318 full-term neonates (2 studies used the same cohort of infants). [18][19][20][21][22][23][24][25][26][27][28] These studies all met the guidelines outlined in the Strengthening the Reporting of Observational Studies in Epidemiology statement regarding quality and bias (Table II; available at www.jpeds.com). 17 Overall, all preterm subgroups showed atypical brain microstructure at term-equivalent age when compared with a full-term group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These 11 studies included DTI data from 554 very preterm, 575 moderate-late preterm, and 318 full-term neonates (2 studies used the same cohort of infants). [18][19][20][21][22][23][24][25][26][27][28] These studies all met the guidelines outlined in the Strengthening the Reporting of Observational Studies in Epidemiology statement regarding quality and bias (Table II; available at www.jpeds.com). 17 Overall, all preterm subgroups showed atypical brain microstructure at term-equivalent age when compared with a full-term group.…”
Section: Resultsmentioning
confidence: 99%
“…24 The estimates of the percentage of the white matter skeleton with a lowered fractional anisotropy ranged between one-third, approximately 59%,and approximately 45%-67%. 24,26,27 The very preterm group seems to show myelogenesis, which is lagging behind the moderate-late preterm group at term-equivalent age, with early myelinating regions suffering the greatest adverse effects. This finding is demonstrated by lower fractional anisotropy and higher radial diffusivity in the very preterm group compared with the moderate-late preterm group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if we consider the week of gestation apart from the division before or after the 37th week of gestation, we observed that only a few features depended on the week of gestation such as cost of attention; quality of alertness; peak of excitement; and reaction to sensory input, such as response decrement to tactile stimulation of foot and animate visual and auditory response (Table 2). According to Kelly (2019), neurobehavior in regard to brain structure-function associations generally does not differ between very and moderate-late preterm neonates [22]. Thus, we did not compare our results in the subgroups, in reference to week of gestation.…”
Section: Discussionmentioning
confidence: 86%
“…Besides the studies above which focused on the functional perspective, tractography has also been successfully adopted in neonates to delineate major white matter tracts including the corticospinal tracts and corpus callosum (Berman et al, 2005;Aeby et al, 2009;Bassi et al, 2011;Hasegawa et al, 2011;Thompson et al, 2011). Furthermore, white matter microstructural alterations may be associated with suboptimal neurologics in certain domains at term-equivalent age (TEA) in infants born preterm (Kelly et al, 2019). However, existing studies merely focused on one single perspective (structural or functional) while the joint analysis of both functional and structural characteristics between preterm and term infant brains is very scarce.…”
Section: Introductionmentioning
confidence: 99%